2020
DOI: 10.1021/acs.est.0c03324
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics Disturb Nitrogen Removal in Constructed Wetlands: Responses of Microbes and Macrophytes

Abstract: Nanosized plastics (nanoplastics) releasing into the wastewater may pose a potential threat to biological nitrogen removal. Constructed wetland (CW), a wastewater treatment or shore buffer system, is an important sink of nanoplastics, while it is unclear how nitrogen removal in CWs occurs in response to nanoplastics. Here, we investigated the effects of polystyrene (PS) nanoplastics (0, 10, and 1000 μg/L) on nitrogen removal for 180 days in CWs. The results revealed that total nitrogen removal efficiency decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(37 citation statements)
references
References 53 publications
1
35
1
Order By: Relevance
“…Studies have shown that nitric oxide (NO) reductase, encoded by nirK and located in the membrane periplasm, can be expressed under both aerobic and anaerobic conditions, and has a high affinity for NO . Although research has shown that plants can provide low molecular weight organics and oxygen for microorganisms, , they had a weak effect on the abundance of functional genes in this study ( P > 0.05). Therefore, compared to the effects of temperature, plants, and spatial position, construction type was the primary variable related to the distribution of functional genes of nxrA , amoA , nosZ , mmoX , and phoD , while it had little effect on the abundance of nirK .…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Studies have shown that nitric oxide (NO) reductase, encoded by nirK and located in the membrane periplasm, can be expressed under both aerobic and anaerobic conditions, and has a high affinity for NO . Although research has shown that plants can provide low molecular weight organics and oxygen for microorganisms, , they had a weak effect on the abundance of functional genes in this study ( P > 0.05). Therefore, compared to the effects of temperature, plants, and spatial position, construction type was the primary variable related to the distribution of functional genes of nxrA , amoA , nosZ , mmoX , and phoD , while it had little effect on the abundance of nirK .…”
Section: Resultscontrasting
confidence: 69%
“…The number of connections for the HSSF CW was 82, which was much higher than that of the VF (24 connections) and SF (25 connections) CWs. The number of nodes for the HSSF CW was higher than that of the VF and SF CWs, and the average degree shows that the HSSF CW (4.97) was higher than the VF (2.40) and SF (2.38) CWs (Table ). Network complexity can depend on microbial richness .…”
Section: Resultsmentioning
confidence: 99%
“…The determination methods of ammonia monooxygenase (AMO), nitrite reductase (NIR), and nitrate reductase (NAR) activities has been described in the previous study (Yang et al 2020). (3…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The determination methods of ammonia monooxygenase (AMO), nitrite reductase (NIR), and nitrate reductase (NAR) activities has been described in the previous study (Yang et al 2020).…”
Section: Analysis Methodsmentioning
confidence: 99%